Impact of Expansion of PGY1 Pharmacy Residency Program From 2 to 4 Residents. (October 2021) - Brophy, Alison; Bente, Jessica; Sobolewski, Kristine; DeStefano, Doug; Costello, Jennifer
Purpose: To evaluate the benefits of postgraduate year 1 (PGY1) pharmacy residency program expansion on clinical outcomes, pharmacy services, educational outreach, costs, and preceptor time at a community teaching hospital. Methods: During academic years 2014 to 2016, two PGY1 resident positions existed, expanding to four PGY1 resident positions during 2016 to 2018. Quantitative analyses comparing the aforementioned periods evaluated clinical interventions, adverse drug events prevented, community and hospital educational programs provided, departmental costs, and documented preceptor hours as a result of program growth. The outcomes were assessed using descriptive statistics. Results: The mean number of documented clinical interventions completed by the resident classes with two residents was 2906 when compared to 5324 with four residents. The mean number of prevented adverse drug events was 56 during the years with two residents and 220 in the years with four residents. The number of community outreach programs increased from 2 to 18 per year. The number of resident lectures provided to allied health professionals increased from 11 to 16 sessions per year. The net economic impact associated with two residents in 2014 was +4661 USD, while in 2017 the net impact was −5262 USD. The mean preceptor hours spent per year related to residency activities with two residents was 1005 hours compared to 1109.5 hours with four residents. Conclusion: Through strategic modification, expansion of the PGY1 residency program led to increased documentation of clinical interventions, prevented adverse drug events, and educational programs provided with minimal change in preceptor burden.